Circularly Polarized Luminescence from Helically Chiral N, N, O, O‐Boron‐Chelated Dipyrromethenes. Issue 1 (30th November 2015) - Alnoman, Rua B.; Rihn, Sandra; O'Connor, Daniel C.; Black, Fiona A.; Costello, Bernard; Waddell, Paul G.; Clegg, William; Peacock, Robert D.; Herrebout, Wouter; Knight, Julian G.; Hall, Michael J.
Abstract: Helically chiral N, N, O, O ‐boron chelated dipyrromethenes showed solution‐phase circularly polarized luminescence (CPL) in the red region of the visible spectrum ( λ em (max) from 621 to 663 nm). The parent dipyrromethene is desymmetrised through O chelation of boron by the 3, 5‐ ortho ‐phenolic substituents, inducing a helical chirality in the fluorophore. The combination of high luminescence dissymmetry factors (| g lum | up to 4.7 ×10 −3 ) and fluorescence quantum yields ( Φ F up to 0.73) gave exceptionally efficient circularly polarized red emission from these simple small organic fluorophores, enabling future application in CPL‐based bioimaging. Abstract : Absolute stereochemistry : Helically chiral N, N, O, O ‐boron chelated dipyrromethenes showed solution‐phase circularly polarized luminescence (CPL) in the red region of the visible spectrum. The parent dipyrromethene is desymmetrised through O chelation of boron by the 3, 5‐ ortho ‐phenolic substituents, inducing a helical chirality in the fluorophore (see figure).